Promoting Enrichment of Living Conditions: Indispensable Goal of all Individuals (Indian Journal of Social Science and Literature (IJSSL), 2024)
The individuals, belonging to all occupations, communities, categories and socio-economic backgrounds have one of the major goals of individuals of promoting enrichment of living conditions. In order to achieve this goal, they are required to augment information in terms of different types of subjects and concepts. Furthermore, they are required to reinforce the traits of morality, ethics, diligence and conscientiousness. In addition, individuals need to understand that there are some job duties, which are carried out on an individual basis, whereas, there are others, which are implemented through working in co-ordination with other individuals. One of the important aspects that needs to be taken into account is, individuals should not be disheartened due to problems and challenging situations. One needs to ensure, they are aware in terms of different job duties and methodologies. In addition, they need to augment confidence levels and overcome the feelings of apprehensiveness and vulnerability. Furthermore, all types of problems and challenging situations need to be prevented from giving rise to impediments within the course of putting into operation different types of tasks and activities. Therefore, it is understood on a comprehensive basis that promoting enrichment of living conditions is an indispensable goal of all individuals. The main concepts that are taken into account in this research paper are, understanding the meaning and significance of promoting enrichment of living conditions, measures to be put into operation in promoting enrichment of living conditions and advantages of promoting enrichment of living conditions.